Comparative study of patient outcomes between direct to implant and two-stage implant-based breast reconstruction after mastectomy. Issue 10 (October 2021) - Caputo, Glenda Giorgia; Vigato, Enrico; Rampino Cordaro, Emanuele; Parodi, Pier Camillo; Governa, Maurizio
Summary: Background: Breast reconstruction plays a central role in the outcome management of patients with breast cancer, particularly in terms of quality of life (QoL), which must be weighed carefully when considering the available surgical options. In the context of implant-based breast reconstruction, immediate replacement with prosthesis (direct-to-implant (DTI)) and acellular dermal matrix (ADM) is gaining popularity, at the expense of the traditional two-stage implant-based breast reconstruction with tissue expander (TE), and the literature suggests that patients tend to prefer interventions with "immediate" therapeutic efficacy and aesthetic satisfaction that obviate the need for further invasive surgery. We investigated this hypothesis by administering the BREAST-Q™ questionnaire to two groups of patients who had undergone the respective procedures. Methods: We performed a cross-sectional observational study of 192 consecutive mastectomy patients who received implant-based reconstruction, comparing health-related quality of life (HR-QoL), patient-related outcomes (PROs) and satisfaction in patients who had undergone immediate dual plane DTI with ADM (96) versus the two-stage submuscular approach (96). We also counted the number of surgeries required in each group to achieve a definitive outcome. Findings: Our study revealed no major differences in terms of QoL scores, with the two approaches being largely comparable. However, single-stage reconstruction seems to offer the additional advantages of better satisfaction with the care received, sparing the patient temporary body image dissatisfaction and reducing the number of surgeries required, thereby lessening the burden on the patient, the healthcare system and society as a whole.